Experiences and opinions of first-year students at a previously disadvantaged medical university in South Africa about alcohol consumption - Indiran Govender; Kathryn Nel; Morongwa M. Mogotsi (South African Family Practice)
Background: The use of alcohol amongst first-year students in institutions of higher learning is problematic as it often leads to social and academic problems, for instance high dropout rates and high-risk sexual behaviour. Research on first-year students’ opinions regarding their own use of alcohol at the University of Limpopo, Medunsa Campus, was seen as pertinent as this institution trains medical doctors, dentists and other health professionals. The findings could inform appropriate interventions by policy-makers at the institution. This paper presents the qualitative data nested from a larger study on alcohol use among first-year medical students.